Duelling Ecclesiologies 1640s Religious Independency in Katherine Chidley's Separatism vs. Thomas Edwards's Presbyterianism - Elliott, Peter J. 1943- (2017)
The broader clash between Charles I and Parliament that became the English Civil Wars was reflected in the narrower battlefront of ecclesiology. With the collapse of censorship, Katherine Chidley's separatism, already formed by the 1620s, achieved an audience in 1641 with her first publication which, ironically, championed the less radical position (and newly coined term) of Independency. Her publication was in response to Thomas Edwards who was striving to ensure Presbyterianism became the new established church. The tension between the two demonstrates the continuity between Elizabethan Brownism and mid-seventeenth-century English separatism, the complexity of the relationship between Independency and separatism, and the rivalry between Presbyterians and Independents/separatists for legitimacy and predominance. The Chidley-Edwards duel sheds light on the multiple conflicts of the day when the magnitude of the stakes involved were captured succinctly in the previous monarch's maxim: No bishop, no king, no nobility. The new position of Independency emerges more clearly through their debate.